Gene and Gene-Environment Risk Factors in Sudden Undexpected Death in Infants - E. Hunt, Carl; R. Hauck, Fern (Current Pediatric Reviews, 2010)
Sequencing of the human genome has expanded our understanding of the molecular basis of many diseases and the complexity of genotype-phenotype relationships. Knowing the genotype does not define the clinical characteristics or phenotype, however, since phenotype is also influenced by gene-gene and gene-environment interactions. Studies in SIDS infants have now identified polymorphisms in 25 genes that are present in increased frequency compared to controls. These include polymorphisms in 8 cardiac channelopathy genes, 3 genes related to serotonin (5-HT), 7 genes related to autonomic nervous system development, 6 genes related to inflammation, and 1 gene related to energy production. The polymorphisms related to cardiac channelopathies and 5-HT have been confirmed in several reports. Confirmation is less robust, however, for the polymorphisms in other genes, in particular as related to energy production. We still know very little about the associated clinical phenotypes and the environmental perturbations required to unmask antemortem phenotypes having increased risk for sudden unexpected death in infants (SUDI). The recent identification of multiple genetic risk factors for SIDS and enhanced understanding of gene-environment interactions are contributing to our knowledge related to SUDI. The challenge now is to capitalize on these hypothesis-generating studies to identify opportunities for effective assessment and intervention in infants who will otherwise die suddenly and unexpectedly. This review summarizes current knowledge regarding gene and gene-environment risk factors that interact to yield phenotypes susceptible to SUDI.
Keywords: serotonin (5-HT)